The shadows of time in Nicholas Sparks's / Abang Moasili Abg Abd Samad - Abg Abd Samad, Abang Moasili (2006)
This study was carried out to explore The Shadows of Time in Nicholas Sparks's, The Rescue. The objective of this study was to find out how the author applied the concept in his book and thus, foreshadow the events that were to come at the end of the story. Based on the hypothesis that he aims at foreshadowing the event in his novel, a combination of qualitative analysis and close reading is used for the findings and discussion.